Sedated and unsedated gastroscopy has no influence on the outcomes of patients with gastric cancer: a retrospective study - Chengke Yin; Yiwu Sun; Jie Liang; Xin Sui; Zhaoyi He; Ailing Song; Wenjia Xu; Lei Zhang; Yufei Sun; Jingshun Zhao; Fei Han (BMC Cancer)
Abstract Background Different anesthetic drugs and techniques may affect survival outcomes for gastric cancer (GC) after surgery. In this study, we investigated the association between sedated and unsedated gastroscopy on survival outcomes in patients with GC after surgery. Methods This was a retrospective study of patients who were diagnosed with GC by gastroscopy and underwent gastrectomy from January 2013 to December 2017. They were grouped based on the examination modality: propofol-based sedated gastroscopy or unsedated gastroscopy. Propensity score matching (PSM) was used to balance the baseline variables. Survival outcomes and distant metastases were compared between these two groups. Results Finally, 673 patients were enrolled, 160 in the sedated gastroscopy group and 513 in the unsedated gastroscopy group. After PSM, there were 160 patients in each group. There was no significant difference in overall survival outcomes in the sedated gastroscopy group compared to the unsedated gastroscopy group before PSM (HR = 0.761, 95% CI: 0.531–1.091, P = 0.139) or after PSM (HR = 0.874, 95% CI: 0.564–1.355, P = 0.547). There was no significant difference in the incidence of distant metastases between the two groups before PSM (16.9% vs. 20.7%, P = 0.294) or after PSM (16.9% vs. 23.8%, P = 0.126). To confirm that our patients behaved similarly to other studies, we performed a multivariate analysis and the results showed that sex, pathological TNM stage, Borrmann type, adjuvant treatment, and surgical resection range were all independent factors affecting survival outcomes in our patients. Conclusion Our results showed no significant difference in the effects of sedated gastroscopy vs. unsedated gastroscopy on survival outcomes or distant metastases of patients after gastrectomy for GC.